Kebutuhan informasi pada keluarga pasien di intensive care unit: A scoping review - Supriyadi, Yadi; Kosasih, Cecep Eli; Nuraeni, Aan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The families of patients play a crucial role in supporting the care and recovery process of patients in the Intensive Care Unit (ICU). One critical aspect of this role is the need for comprehensive and relevant information about the patient's condition and care in the ICU. Purpose: To explore the information needs of families of patients in the intensive care unit (ICU). Method: Literature search was conducted in Scopus, PubMed, and CINAHL databases and google scholar search engine. The initial articles found were 12,056, then 9 articles were included in the study. Data were extracted and synthesized to provide a comprehensive picture of the information needs of patient families in the ICU. Results: Families need in-depth information about the patient's condition, the care provided, and the medical team involved in the care. A variety of communication and education methods have been used to meet this information need, including the use of easy-to-understand language and the provision of written or visual materials. Education that is tailored to the family's preferences and needs and pays attention to the language used is key to providing effective support to families of patients in the ICU. Conclusion: Families play a vital role in understanding and addressing the informational needs of ICU patient families. Enhancing communication and education tailored to family needs can improve family involvement in patient care and overall care outcomes. Keywords: Information Needs; Intensive Care Unit; Patient's Family. Pendahuluan: Keluarga pasien memiliki peran penting dalam mendukung proses perawatan dan pemulihan pasien di Intensive Care Unit (ICU). Salah satu aspek krusial dalam peran keluarga ini adalah kebutuhan akan informasi yang komprehensif dan relevan tentang kondisi dan perawatan pasien di ICU. Tujuan: Untuk mengeksplorasi kebutuhan informasi keluarga pasien di intensive care unit (ICU). Metode: Pencarian literatur dilakukan di database Scopus, PubMed, dan CINAHL serta search engine Google Scholar. Artikel awal yang ditemukan adalah 12,056, kemudian 9 artikel disertakan dalam penelitian. Data diekstraksi dan disintesis untuk memberikan gambaran komprehensif tentang kebutuhan informasi keluarga pasien di ICU. Hasil: Keluarga membutuhkan informasi yang mendalam tentang kondisi pasien, perawatan yang diberikan, dan tim medis yang terlibat dalam perawatan. Berbagai metode komunikasi dan edukasi telah digunakan untuk memenuhi kebutuhan informasi ini, termasuk penggunaan bahasa yang mudah dipahami dan penyediaan materi tertulis atau visual. Edukasi yang disesuaikan dengan preferensi dan kebutuhan keluarga serta memperhatikan bahasa yang digunakan menjadi kunci dalam memberikan dukungan yang efektif kepada keluarga pasien di ICU. Simpulan: Keluarga memiliki peran penting dalam memahami dan memenuhi kebutuhan informasi keluarga pasien di ICU. Memperbaiki komunikasi dan edukasi yang disesuaikan dengan kebutuhan keluarga dapat meningkatkan keterlibatan keluarga dalam perawatan pasien serta meningkatkan hasil perawatan secara keseluruhan. Kata Kunci: Intensive Care Unit; Kebutuhan Informasi; Keluarga Pasien.